KEDWIBAHASAAN PADA GENERASI MUDA LAMAHOLOT DI KECAMATAN LARANTUKA KABUPATEN FLORES TIMUR - Ola, Simon Sabon; Makan Malay, Narantoputrayadi (Jurnal Lazuardi, 2023)
This article focuses on the use of language by the young Lamaholot generation in Larantuka City. The study in this article aims to describe language use by the younger generation in bilingual situations. The concept underlying this study is bilingualism and the realm of language use. Meanwhile what is referred to is Sociolinguistic Theory which emphasizes the use of language in the social context of its speakers. Analysis of data on language use by the younger generation of Lamaholot in Larantuka City shows that their language choices tend to be unbalanced even though their bilingualism is categorized as balanced. . This is predominantly determined by the variables involved. In any setting with any topic, if the participants in the conversation consist of fellow Lamaholot people, then the language of choice used is Lamaholot. This condition is interpreted as an accommodating attitude of the young generation of Lamaholot speakers in Larantuka City. This situation of language use does not have the potential to create language hegemony between Lamaholot, Indonesian and Larantuka Malay.